Nursing care for hospitalized older adults - fall accidents versus safe mobility: a scoping review - Esther Mourão Nicoli; Frances Valéria Costa e Silva; Luciana Guimarães Assad; Camila Castanho Cardinelli; Raquel Azevedo Alves; Samara Gonçalves de Oliveira (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to map the constituent elements of the safe mobility concept present in hospital care for older adults. Methods: a scoping review of 35 articles searched in databases and gray literature - BDENF/VHL, Scopus, CINAHL/EBSCO, Embase, Web of Science, PEDro, MEDLINE/PubMed and CAPES Theses and Dissertations Catalog. No time or language cut-off was established. Results: none of the studies presented a clear safe mobility concept, however its constituent elements involve factors related to patient (behavioral factors, conditions, diseases, signs and symptoms, nutritional status, age, balance, strength, gait quality, sleep), the institution (environment, treatment devices, guidelines, medications and polypharmacy, material and human resources and clothing/shoes) and the nature of the interventions (related to the patient, institution and family). Final Considerations: the constituent elements of safe mobility express hospital units' capacity to guarantee care and protection from fall accidents for hospitalized older adults.